ANALYSIS OF QUALITY MANAGEMENT IN THE SUSTAINABLE PALM OIL INDUSTRY IN RIAU: A QUALITATIVE STUDY OF INDEPENDENT FARMERS - Rahman, Fathi Habibatur; Arif, Nina Fapari; Rifani, Siti Khusnul (Universitas Putera Batam, 2025)
This study aims to analyse quality management in the sustainable palm oil industry in Riau Province, focusing on the practices of independent palm oil farmers. Using a qualitative approach through surveys and in-depth interviews with 30-40 farmers selected through purposive sampling, this study explores the understanding, challenges, and quality management strategies applied by farmers. The results indicate that while farmers' understanding of quality standards and cultivation practices is already quite good, there is a gap between theory and practice due to limitations in capital, access to technology, and institutional support. Training and mentoring have proven effective in improving knowledge and quality management practices; however, challenges such as fluctuations in TBS prices and inadequate infrastructure still hinder optimal implementation. Key factors influencing quality management include raw material quality, workforce competence, institutional support, and infrastructure. Recommended strengthening strategies include capacity building through training, institutional strengthening, accelerated certification, infrastructure improvement, and multi-stakeholder synergy. The findings of this study provide a comprehensive overview of the quality management conditions of independent oil palm farmers in Riau and serve as the basis for policy recommendations and training programmes to support the sustainability and competitiveness of the oil palm industry.